The Service Sector in Lower-Income Asian Economies - Gemma Estrada; Yubraj Acharya; Aaron Batten; Peter Brimble; Poullang Doung; Mirzo Iskandar Gulamov; Mohammad Zahid Hossain; Dominic Mellor; Donghyun Park; Shamsur Rahman (Asian Development Bank (ADB), 2013)
In the past 10 years, the service sector has been a significant contributor to overall economic growth in Bangladesh, Cambodia, Nepal, Papua New Guinea, Uzbekistan, and Viet Nam. Sector growth has been supported by strong industrial growth in some while in others the critical factors have been liberalization, structural reforms, government support, and foreign investments. In order to increase the labor productivity of the sector and realize its potential to contribute to inclusive growth, these countries must address gaps in human capital and the higher costs of setting up new businesses and of doing business that stifle entrepreneurship and private enterprise. These impediments also stand in the way of developing the industry sector and of broader economic growth and development. Policy reforms that ease those impediments will help to achieve balanced growth in which the service and industry sectors support and reinforce each other. As services tend to be more labor intensive, they can foster inclusive growth by serving as an engine for creating jobs.
hdl:11540/2319
Keywords: O14; O40; 330; services; structural change; growth; Asia